Fulfilment of knowledge expectations among family members of patients undergoing arthroplasty: A European perspective - Sigurdardottir, Árún K.; Leino-Kilpi, Helena; Charalambous, Andreas; Katajisto, Jouko K.; Stark, Åsa Johansson; Sourtzi, Panayota A.; Zabalegui-Yárnoz, Adelaida; Valkeapää, Kirsi (My University, 2015)
In the recovery process of arthroplasty patients, their family members play an important role due to short hospital stay and increased age of patients. Family members need to have knowledge to be able to support the patient. The aim of this study was to explore expected and received knowledge in family members of arthroplasty patients and describe the relationships between the differences in received and expected knowledge and background factors, country, information and control preferences and access to knowledge. The study was conducted in six European countries (Cyprus, Greece, Finland, Iceland, Spain and Sweden). The study design was cross-cultural, prospective and comparative with two measurement points: pre-operative and at discharge from hospital. Knowledge Expectations of significant other-scale and Krantz Health Opinion Survey were used before surgery and Received Knowledge of significant other-scale and Access to Knowledge at discharge. Patients undergoing elective hip or knee arthroplasty in seventeen hospitals were asked to identify one family member. The sample size was decided by power calculation. A total of 615 participants answered the questionnaires at both measurements. Family members perceived to receive less knowledge than they expected to have, most unfulfilled knowledge expectations were in the financial, social and experiential dimensions of knowledge. Seventy-four per cent of participants had unfulfilled knowledge expectations. Increased access to information from healthcare providers decreased the difference between received and expected knowledge. Compared to family members in southern Europe, those in the Nordic countries had more unfulfilled knowledge expectations and less access to information from healthcare providers. The evidence from this study highlights the need to involve the family members in the educational approach.
Keywords: Arthroplasty; Family members; International perspectives; Knowledge expectations; Osteoarthritis; Patient education